AUTOMATED ROOM LIGHTING AND FAN SYSTEM FOR ENERGY EFFICIENCY IN SMART HOMES - Jason Fernando; Endah Setyaningsih; Titin Fatimah (TESLA: Jurnal Teknik Elektro, 2025)
Energy waste can be caused by the uncontrolled use of electronic devices. This study develops an ESP32-based automation system to optimize the automatic operation of room lighting and fans as an effort toward energy saving and the smart home concept. The research method is system design, divided into two main parts: system 1, which regulates lighting using PIR and BH1750 sensors, and system 2, which controls a fan and desk lamp using an ultrasonic sensor, DHT11, and an AS608 fingerprint sensor. Both systems communicate through ESP-NOW to ensure coordination in device operation. The ESP32-based system was chosen for its capability of integrating wireless connectivity, relatively low power consumption, and support for multiple communication protocols, making it suitable for smart home applications. In addition, the use of biometric sensors provides added value in the form of personalized control, which is rarely found in similar studies, making the system not only efficient but also adaptive to users’ specific needs. Experimental results show that the system can adjust lighting and fan speed according to designed scenarios and user preferences. The room lighting was maintained within the range of 260 lux to 385 lux when occupied, and the fan remained active when the temperature exceeded 25°C to support air circulation, but automatically turned off when the temperature fell below 25°C to save energy. The key finding of this study is that energy savings can be achieved through condition-based load control, reduction of unnecessary power consumption, and personalization via fingerprint sensors. The integration of ESP-NOW and biometrics makes this design an innovative approach toward a user-oriented, energy-efficient smart home. Abstrak Pemborosan energi salah satunya dapat disebabkan oleh penggunaan perangkat elektronik yang tidak terkontrol. Penelitian ini mengembangkan sistem otomatisasi berbasis ESP32 untuk mengoptimalkan penggunaan lampu ruang dan kipas angin secara otomatis, sebagai upaya penghematan energi menuju konsep smart home. Metoda penelitian berupa perancangan sistem dengan dua bagian utama, yaitu sistem 1 yang mengatur pencahayaan menggunakan sensor PIR dan BH1750, serta sistem 2 yang mengontrol kipas dan lampu meja dengan sensor ultrasonik, DHT11, dan sensor sidik jari AS608. Kedua sistem berkomunikasi melalui ESP-NOW untuk memastikan koordinasi dalam pengoperasian perangkat. Pemilihan sistem berbasis ESP32 didasarkan pada kemampuannya dalam integrasi konektivitas nirkabel, konsumsi daya yang relatif rendah, serta dukungan terhadap berbagai protokol komunikasi sehingga sesuai untuk aplikasi smart home. Selain itu, penggunaan sensor biometrik memberikan nilai tambah berupa personalisasi kontrol yang jarang ditemukan pada penelitian sejenis, menjadikan sistem ini tidak hanya efisien tetapi juga adaptif terhadap kebutuhan spesifik pengguna. Hasil pengujian menunjukkan sistem mampu menyesuaikan pencahayaan dan kecepatan kipas sesuai skenario yang dirancang dan preferensi pengguna. Lampu ruang diatur selalu berada pada rentang 260 lux sampai dengan 385 lux, jika ruangan digunakan dan kipas angin tetap menyala jika suhu melebihi 25°C, untuk membantu sirkulasi udara, tetapi jika suhu turun di bawah 25°C, kipas mati untuk menghemat daya. Temuan penting penelitian ini adalah bahwa penghematan energi dapat dicapai melalui pengendalian beban listrik berbasis kondisi aktual, pengurangan konsumsi daya yang tidak diperlukan, serta penerapan personalisasi dengan sensor sidik jari. Integrasi ESP-NOW dan biometrik menjadikan rancangan ini sebagai inovasi menuju konsep smart home hemat energi dan berorientasi pengguna.